2015
DOI: 10.1002/jcu.22268
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular function by three‐dimensional speckle‐tracking echocardiography in well‐treated type 2 diabetes patients with or without hypertension

Abstract: Early-stage diabetic patients showed an impaired left ventricular strain that was worsened by coexistent hypertension, although blood glucose and blood pressure were well controlled. Three-dimensional speckle-tracking echocardiography was able to detect these subclinical changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 33 publications
(33 reference statements)
8
23
0
1
Order By: Relevance
“…In a limited number of studies, LA volume has been accurately quantified by three‐dimensional echocardiography using both reconstructive and real‐time techniques . STI can also be used to estimate deformation in three‐dimensions independently of angle, providing additional information such as the longitudinal, circumferential, radial, and area strain …”
Section: Discussionmentioning
confidence: 99%
“…In a limited number of studies, LA volume has been accurately quantified by three‐dimensional echocardiography using both reconstructive and real‐time techniques . STI can also be used to estimate deformation in three‐dimensions independently of angle, providing additional information such as the longitudinal, circumferential, radial, and area strain …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Enomoto et al. found that patients with poorly controlled DM had much worse GLS regardless of whether or not there was coexisting HTN . As of now, the exact pathophysiologic mechanism for this dysfunction is unknown, but there is some suspicion that microvasculopathy and inhibition of compensatory angiogenesis may be responsible via degeneration of myocardial fibers and reduced perfusion .…”
Section: Discussionmentioning
confidence: 99%
“…28 Recently, Enomoto et al found that patients with poorly controlled DM had much worse GLS regardless of whether or not there was coexisting HTN. 29,30 As of now, the exact pathophysiologic mechanism for this dysfunction is unknown, but there is some suspicion that microvasculopathy and inhibition of compensatory angiogenesis may be responsible via degeneration of myocardial fibers and reduced perfusion. 30 In addition, the extracellular matrix in diabetics is known to poorly adjust and compensate for progressively worsening cardiac demands to the point that longitudinal strain decreases.…”
Section: Diabetesmentioning
confidence: 99%
“…It was found that 25% untwist was related to oxygen uptake, which can be used as an independent predictor of aerobic exercise ability and a good indicator of cardiac diastolic function in patients with HF . 3D‐STE can also detect early left ventricular dysfunction caused by hypertrophic cardiomyopathy, essential hypertension, type 2 diabetes mellitus, and chemotherapy drugs . In addition to evaluating LV myocardial motion, 3D‐STE can also evaluate the left atrium, right atrium, and right ventricle …”
Section: D‐ste In Assessing Myocardial Motionmentioning
confidence: 99%